Evaluasi Implementasi Hukum Pidana terhadap Kasus Kejahatan Lingkungan di Kawasan Hutan Lindung: Studi Kualitatif-Etnografis - Kossay, Methodius; Putra, Rengga Kusuma; Salwa, Athiyah (LPPM Universitas Sains dan Teknologi Komputer, 2024)
Protected forests play a crucial role in preserving biodiversity and mitigating climate change. However, these areas face increasing threats from illegal activities, such as logging and land encroachment, which compromise environmental stability and result in significant economic losses. This study evaluates the implementation of criminal law in addressing environmental crimes within Indonesia's protected forest areas, focusing on the effectiveness and challenges encountered in enforcement. A qualitative ethnographic approach was employed, involving direct observation, in-depth interviews, and focus group discussions (FGDs) with local communities, law enforcement officials, and other stakeholders. The findings reveal that the effectiveness of law enforcement is hindered by several key factors: economic dependency on illegal activities, limited capacity and resources of law enforcement agencies, and external pressures from vested interests. Additionally, the lack of public awareness and inconsistent legal implementation exacerbate these challenges. Despite existing regulations, enforcement remains insufficient to deter environmental crimes or provide lasting protection for critical ecosystems. This study contributes to the understanding of the socio-economic and cultural dynamics that influence the effectiveness of environmental law enforcement. It underscores the need for a holistic strategy that integrates legal, economic, and community-based approaches. Recommendations include strengthening the capacity of law enforcement agencies, fostering public awareness through educational programs, and involving local communities and traditional leaders in collaborative conservation efforts. By addressing these gaps, the research provides actionable insights to enhance the preservation of protected forests in Indonesia and supports the development of more sustainable and inclusive environmental policies